2017
DOI: 10.1097/acm.0000000000001465
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year MD Programs: Perspectives From the Consortium of Accelerated Medical Pathway Programs (CAMPP)

Abstract: In the last decade, there has been renewed interest in three-year MD pathway programs. In 2015, with support from the Josiah Macy Jr., Foundation, eight North American medical schools with three-year accelerated medical pathway programs formed the Consortium of Accelerated Medical Pathway Programs (CAMPP). The schools are two campuses of the Medical College of Wisconsin; McMaster University Michael G. DeGroote School of Medicine; Mercer University School of Medicine; New York University School of Medicine; Pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 10 publications
3
32
0
2
Order By: Relevance
“…Figure 2 documents the rise in total medical students from 1930 to 2017 juxtaposed against percentages of accredited allopathic medical schools with 3-year curriculum over the same period [9,12,20,22–38]. As can be seen in Figure 2, the greatest percentage of medical schools with a 3-year program occurred in the WWII era (≈90%) followed by the 1970s (≈40%).…”
Section: Detailed Historymentioning
confidence: 92%
See 4 more Smart Citations
“…Figure 2 documents the rise in total medical students from 1930 to 2017 juxtaposed against percentages of accredited allopathic medical schools with 3-year curriculum over the same period [9,12,20,22–38]. As can be seen in Figure 2, the greatest percentage of medical schools with a 3-year program occurred in the WWII era (≈90%) followed by the 1970s (≈40%).…”
Section: Detailed Historymentioning
confidence: 92%
“…At Ohio State, the mean satisfaction score of faculty participating in the 3-year curriculum was 60.5 out of 100 (range of 34–93), with 50% of faculty favored returning to a 4-year MD program [20]. Although studies showed no major difference in performance between 3-year and 4-year students, as measured by USMLE scores and residency match results, by the end of the 1970s most 3-year MD programs were discontinued in favor of 4-year curricula [13,17,21,22]. Indeed, after the 1973–1974 academic year, a persistent decline in enrollment in these programs occurred, with 2,434 3-year MD students in 1974–1975 declining to 1,455 in 1978–1979 [23].…”
Section: Detailed Historymentioning
confidence: 99%
See 3 more Smart Citations